Il bordo opaco. Pensare lo schermo, pensare la superficie - Anna Caterina Dalmasso (Rivista di Estetica, 2014)
The screen’s frame outlines a separation, an ontological and semiotic cut between the real space and the view contained within its aperture. While it inherits such a border from the tradition of pictorial representation, the screen’s surface constitute itself as an overlapping structure that encroaches and puts into question the existence of its own boundaries. Drawing on some references to the notion of “screen” in Merleau-Ponty’s work, I would like to delineate and interrogate the peculiar nature of the borders that the screens ex-pose and im-pose to its surface. Addressing the notion of screen, as both an optical and conceptual apparatus, I aim at describing the way the “screen” and its “surface” can be thought as a topological figure, more as a cavity, a relief or fold, than as a frame of vision.